A brief review of frequency, radiation pattern, polarization, and compound reconfigurable antennas for 5G applications - Kamran Shereen, M. (Springer New York LLC, 2019)
All antennas in which frequency and radiation patterns can be modified in a reversible and controlled manner are known as reconfigurable antennas. They are different from other antennas, as their mechanism of reconfiguration is located within the antenna and not controlled by an external beam. For reconfigurable antennas, the potential is not to increase the performance of the antenna in a significantly changed state or to meet the needs of dynamics and efficacy. This study will discuss various aspects related to antennas that are frequency-reconfigurable, their applications and execution frequencies, change in polarization, and changes in far-field patterns or operating frequencies to better deal with changing system parameters. For the reconfigurable antennas in this paper, some past and recent applications will be reviewed, along with examples of their implementation. The arrays and moving mechanical parts are explained, along with recently introduced semiconductor factors, and the tunable material technologies that should be applicable for reconfigurable antennas. Â© 2019, Springer Science+Business Media, LLC, part of Springer Nature.